Epidemiology, clinical manifestations, and diagnosis of chikungunya fever: Lessons learned from the re-emerging epidemic - Mohan Alladi; Kiran D.H.N; Manohar I; Kumar D (Wolters Kluwer Medknow Publications, 2010)
Chikungunya fever, caused by "Chikungunya virus," is an arbovirus disease transmitted by the bite of infected mosquitoes belonging to the genus Aedes. Chikungunya fever epidemics have been reported from several countries around the world. The disease that was silent for nearly 32 years re-emerged in the October 2005 outbreak in India that is still ongoing. The incubation period ranges from 3 to 12 days. The onset is usually abrupt and the acute stage is characterized by sudden onset with high-grade fever, severe arthralgias, myalgias, and skin rash. Swollen tender joints and crippling arthritis are usually evident. In the chronic stage, relapses that include sensation of fever, asthenia, exacerbation of arthralgias, inflammatory polyarthritis, and stiffness may be evident. Neurological, ocular, and mucocutaneous manifestations have also been described. Chronic arthritis may develop in about 15% of the patients. Viral culture is the gold standard for the diagnosis of Chikungunya fever. Reverse transcription polymerase chain reaction and real-time loop-mediated isothermal amplification have also been found to be useful. Serodiagnostic methods for the detection of immunoglobulin M and immunoglobulin G antibodies against Chikungunya virus are more frequently used. Chikungunya is a self-limiting disease; however, severe manifestations such as meningoencephalitis, fulminant hepatitis, and bleeding manifestations may sometimes be life-threatening. Treatment is symptomatic and supportive. Prevention by educating the community and public health officials, vector control measures appear to be the best approach at controlling Chikungunya fever as no commercially available vaccine is available for public use in India for this condition presently.